1977
DOI: 10.1111/j.1469-8137.1977.tb02190.x
|View full text |Cite
|
Sign up to set email alerts
|

THE EFFECT OF TIME OF EXPOSURE TO SULPHUR DIOXIDE ON POTASSIUM LOSS FROM AND PHOTOSYNTHESIS IN THE LICHEN, CLADINA RANGIFERINA (L.) HARM.

Abstract: SUMMARYSamples of the lichen, Cladina rangiferina., were exposed to various concentrations of aqueous SO2 for 10 min, and 0.5, 1, 3, 6 and 12 h. K*-efflux curves (K* release versus ppm SO2 (wt/wt, aqueous)) were constructed for each exposure period. In separate experiments, the photosynthetic ' "^C fixation rates were measured after the SO2 exposures. Plots of % total ^^C fixation v. ppm SO2 (wt/wt, aqueous) were found to be linear for the 3 h and 6 h exposure periods, while plots of log (% total ^'C fixation)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

1977
1977
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 18 publications
1
13
0
1
Order By: Relevance
“…As the opposite situation was apparent, it is suggested that large amounts of trace metals accumulating in the lichens result in the removal of 137 Cs. Several studies demonstrated an enlarged loss of potassium following an exposure of lichens to trace elements (Puckett 1976;Nieboer et al 1979;Tarhanen et al 1999;Hyvärinen et al 2000;Cabral 2003;Mrak et al 2007) or to SO 2 Tomassini et al 1977). Low K contents were observed also for lichens in environments polluted by trace metals and other contaminants (Garty et al , 1997c(Garty et al , 1998a(Garty et al , 2002cAdamo et al 2003;Williamson et al 2004;Tretiach et al 2007).…”
Section: The Chernobyl Accidentmentioning
confidence: 98%
“…As the opposite situation was apparent, it is suggested that large amounts of trace metals accumulating in the lichens result in the removal of 137 Cs. Several studies demonstrated an enlarged loss of potassium following an exposure of lichens to trace elements (Puckett 1976;Nieboer et al 1979;Tarhanen et al 1999;Hyvärinen et al 2000;Cabral 2003;Mrak et al 2007) or to SO 2 Tomassini et al 1977). Low K contents were observed also for lichens in environments polluted by trace metals and other contaminants (Garty et al , 1997c(Garty et al , 1998a(Garty et al , 2002cAdamo et al 2003;Williamson et al 2004;Tretiach et al 2007).…”
Section: The Chernobyl Accidentmentioning
confidence: 98%
“…Although the K"*" efflux rate increased with the total available SO2 per unit weight of lichen, the x-intercept of extrapolations, and hence evaluated sensitivity, was only minimally affected. This aspect is considered in more detail by Tomassini et al (1977). Table 1 shows that K"^ loss during a 3 h exposure was induced in sensitive species by equivalent gaseous concentrations less than 1 ppm while other species were unaffected by levels in excess of 2 ppm for this period.…”
Section: The Relative Sensitivities Of Lichen Speciesmentioning
confidence: 99%
“…Controlled experiments investigating the effect of exposure to SO 2 were described by Puckett et al. (1977) and Tomassini et al. (1977).…”
Section: Introductionmentioning
confidence: 99%